2018
DOI: 10.1177/0145721718782148
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Among Adults With Type 1 Diabetes Mellitus and Implications for Self-Management: An Integrative Review

Abstract: Purpose The aim of this review was to integrate empirical and theoretical literature on fatigue among adults with type 1 diabetes mellitus (T1DM). A methodological review using an integrative approach was used. Databases MEDLINE via Pubmed, CINAHL, PsycINFO, and Science Direct were searched for peer-reviewed articles published in English from 2007-2017, using the following search terms and Boolean operators: "Type 1 Diabetes" and "Fatigue." Of 199 articles initially retrieved, 14 were chosen for inclusion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
2
25
0
2
Order By: Relevance
“…Along with other symptoms, fatigue may herald comorbid psychophysiological changes and acute or chronic complications (Fritschi & Quinn, 2010; Kalra & Sahay, 2018). Additionally, fatigue may reduce an individual’s capacity to perform daily activities essential to optimal glucose control (e.g., glucose monitor, preparing a healthy diet, and regular physical activity; Griggs & Morris, 2018). Empirical evidence also suggests that fatigue could be a barrier to adequate self-care (Fritschi & Quinn, 2010; Kirk et al, 2015; Zhu et al, 2018), which is the cornerstone for effective diabetes management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Along with other symptoms, fatigue may herald comorbid psychophysiological changes and acute or chronic complications (Fritschi & Quinn, 2010; Kalra & Sahay, 2018). Additionally, fatigue may reduce an individual’s capacity to perform daily activities essential to optimal glucose control (e.g., glucose monitor, preparing a healthy diet, and regular physical activity; Griggs & Morris, 2018). Empirical evidence also suggests that fatigue could be a barrier to adequate self-care (Fritschi & Quinn, 2010; Kirk et al, 2015; Zhu et al, 2018), which is the cornerstone for effective diabetes management.…”
mentioning
confidence: 99%
“…Previous reviews have been focused on fatigue among people with type 1 diabetes (T1D; Griggs & Morris, 2018; Jensen et al, 2017; Pouwer, 2017). Specifically, Jensen et al (2017) reviewed 10 observational studies and found that the prevalence of fatigue in patients with T1D ranged from 23% to 40%.…”
mentioning
confidence: 99%
“…However, health condition does not influence the accuracy performance of the ensemble classifier; the values are between 97.2% and 97.9% for both window sizes. The complex nature of fatigue and the factors affiliated among adults suffering from T1DM is the reason for the limited number of investigations of the influence of fatigue on this group of patients [63] as well as the lack of papers investigating machine-learning classifications based on fatigue-induced tremors in healthy and T1DM participants. MVC amplitude significantly decreases, and fatigue onset occurs sooner in T1DM participants compared to the control group according to [31].…”
Section: Early and Late Fatigue Recognitionmentioning
confidence: 99%
“…Diabetes fatigue has vicious cyclic relationship with numerous factors, including diabetes symptoms, diabetic complications, other endocrine disorders, emotional distress, and lifestyle factors [16] and, in turn, it negatively influences emotions, lifestyle, and blood sugar control, increasing the risks for physical and psychological diabetes complications [17]. While diabetes fatigue has been conceptualized in several ways [16,17,18,19], the existing conceptual frameworks have been limited in their ability to comprehensively encompass the multidimensional characteristics of fatigue, including those related to biological, psychological, social, and environmental contexts. The dynamic biopsychosocial (DBPS) model provides a dynamic, ecological perspective of health, which views health as being determined by the interactions between biological, psychological, and social dynamics [20], and could be a useful conceptual framework for understanding the multidimensional properties of diabetes fatigue.…”
Section: Introductionmentioning
confidence: 99%